SENSITIVITY PATTERNS OF SOME FLOWERING PLANTS AGAINST SALMONELLA TYPHI AND PSEUDOMONAS AERUGINOSA - Rajan, DR. Jenifer Solomon (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
The medicinal plants have been collected form wild resources and only some species used in larger quantities are cultivated systematically. Many medicinal plants, which were ignored in the past years, but the number of plants still formed in the wild is progressively declining the medicinal value with this situation to acquiring from the wild sources in more important recent trends bening. Reported in cresingly the antimicrobial properties of medicinal plants from different parts of the world .On this basis, the present investigation was focused on the screening of antimicrobial properties ofAsystasia indica Asystasia gangetica Thunbergia alata on selected Pathogenic bacteriaThe main objectives of this work use as follow To Screen the antimicrobial properties of these plants on selected micro organisms.To determine the effectiveness of inhibition on microbes by comparing its activity with known antibiotics.